Exacerbated experimental arthritis in Wiskott–Aldrich syndrome protein deficiency: Modulatory role of regulatory B cells. Issue 9 (15th July 2014) - Bouma, Gerben; Carter, Natalie A.; Recher, Mike; Malinova, Dessislava; Adriani, Marsilio; Notarangelo, Luigi D.; Burns, Siobhan O.; Mauri, Claudia; Thrasher, Adrian J.
<x xml:space="preserve">Abstract</x> Patients deficient in the cytoskeletal regulator Wiskott–Aldrich syndrome protein (WASp) are predisposed to varied autoimmunity, suggesting it has an important controlling role in participating cells. IL‐10‐producing regulatory B (Breg) cells are emerging as important mediators of immunosuppressive activity. In experimental, antigen‐induced arthritis WASp‐deficient (WASp knockout [WAS KO]) mice developed exacerbated disease associated with decreased Breg cells and regulatory T (Treg) cells, but increased Th17 cells in knee‐draining LNs. Arthritic WAS KO mice showed increased serum levels of B‐cell‐activating factor, while their B cells were unresponsive in terms of B‐cell‐activating factor induced survival and IL‐10 production. Adoptive transfer of WT Breg cells ameliorated arthritis in WAS KO recipients and restored a normal balance of Treg and Th17 cells. Mice with B‐cell‐restricted WASp deficiency, however, did not develop exacerbated arthritis, despite exhibiting reduced Breg‐ and Treg‐cell numbers during active disease, and Th17 cells were not increased over equivalent WT levels. These findings support a contributory role for defective Breg cells in the development of WAS‐related autoimmunity, but demonstrate that functional competence in other regulatory populations can be compensatory. A properly regulated cytoskeleton is therefore important for normal Breg‐cell activity and complementation of defects in this lineage is likely to have important therapeutic benefits.